Using Treponemal Assay Signal Strength Cutoff Ratios To Predict Syphilis Infection - Bristow, Claire C. (J Clin Microbiol, 2017)
Syphilis screening with the reverse algorithm, a treponemal test for screening followed by a nontreponemal test if reactive, is increasingly being used. That algorithm has several advantages, including use of an automated screening test, saving on laboratory time and costs, as well as detection of very early syphilis infection. However, under that algorithm, in situations where the treponemal result is positive and the nontreponemal result is nonreactive a second treponemal test must be performed, which may actually lead to inefficiencies in the laboratory. In this issue of the Journal of Clinical Microbiology, Y. F. Fakile et al. (J Clin Microbiol 56:e01165-17, 2017, https://doi.org/10.1128/JCM.01165-17) report the results of their study, which demonstrates the capability of signal strength ratio cutoffs for automated treponemal immunoassays to predict the outcome of repeat treponemal testing. Their findings suggest that anti-treponemal signal strength ratio values above a cutoff value can be used in lieu of repeat treponemal tests.